Perceptions of Saudi dental students on cultural competency - Al-Shehri, Huda A. (Saudi Med J, 2016)
OBJECTIVES: To probe dental students’ perceptions on their cultural competency and international student exchange programs as a way of improving cultural competency training. METHODS: A cross-sectional survey (n=460) was distributed to predoctoral students at the College of Dentistry, King Saud University, Riyadh, Kingdom of Saudi Arabia in May 2014 at the male and female university campuses. Descriptive statistics were carried out using Statistical Package for Social Sciences (p=0.05). RESULTS: It was found that 79.6% of students think that teaching them regarding cultural diversity is important. Only 41% of students thought their dental education teaches them on the importance of volunteerism and philanthropy. Most students (89.8%) think that international student exchanges can enhance their cultural competence. CONCLUSION: In this study, it was found that students believe that cultural competence is important and participation in international student exchange programs can enhance their training.